AB0843-HPR To lead and to follow - experiences from guiding people with rheumatoid arthritis to increased physical activity. the para 2010 study. (23rd January 2014) - Nessen, T.; Opava, C.; Martin, C.; Demmelmaier, I.
Abstract : Background: Lifelong physical activity is important to maintain body functions and prevent co-morbidity in people with rheumatoid arthritis (RA). The PARA 2010 study evaluates a two-year program for the adoption and maintenance of health-enhancing physical activity (HEPA)(1 ) with physiotherapists promoting twice-weekly circuit training at public gyms and moderately intense physical activity on most other days of the week. Furthermore, the physiotherapists guide support groups in specific behavior change techniques such as SMART goal-setting, self-monitoring and relapse prevention strategies. Since such integration of physiological and behavioral aspects is not yet part of mainstream physiotherapy, physiotherapists' perception of their new roles needs to be explored. Objectives: The objective was to explore the experiences of physiotherapists coaching the HEPA program, more specifically to describe their perceived obstacles and facilitators in learning and delivering the program. Methods: Semi-structured interviews were conducted with all 12 physiotherapists (100 % females, median age 41 years, median experience as a physiotherapist 14 years) participating in the program, inquiring their experiences from a preparation course and from their delivery of the HEPA intervention. The interviews were recorded on audio files and transcribed verbatim. Codes, sub-categories, categories and a overarching theme were derived from the text based on content analysis as described by Graneheim and Lundman (2 ). Results: The overarching theme emerging from the analysis was 'From clinical expert to guide'. It was derived from three main categories 'Challenges in the coach role', 'Growing into the coach role' and 'Education and coach support'. Each main category contained a number of subcategories. Thus, 'Challenges in the coach role' contained 'Leading or following the group', 'Individualized coaching', 'Group expectations about being directed', 'Insecurity about task and role', 'Initial stress' and 'Timeframes and logistics'. 'Growing into the coach role' contained 'Reducing steering and control', 'Promoting adoption of HEPA', 'Promoting maintenance of HEPA', 'Confidence in coaching', 'Adapting to the group' and 'Using coaching skills in other contexts'. 'Education and coach support' contained 'Clarification of task and role needed', 'Important with feedback on coaching behavior', 'Feeling included in the project', 'Pros and cons of printed study material' and 'Techniques and support not used'. Conclusions: In conclusion the physiotherapists encountered challenges early on that needed to be addressed for a smoother transition into their task as physio coaches. Furthermore, over time the physiotherapists adopted certain practices that helped them grow into the role of physio coaches to guide groups in changing physical activity behavior. These findings may assist in developing an education and support system that reduces the challenges and promote growth. References: Nordgren B, Fridén C, Demmelmaier I, Bergström G, Opava CH. Long-term health-enhancing physical activity in rheumatoid arthritis - the PARA 2010 study. Study protocol. BMC Public Health 2012 Jun 1;12(1):397 [E-pub ahead of print] Graneheim UH, Lundman B. Qualitative content analysis in nursing research: concepts, procedures and measures to achieve trustworthiness. Nurse Educ Today 2004;24:105-12 Disclosure of Interest: None Declared